Primeiras e eternas memórias de um Professor de Educação Física - Tiago Rodrigues de Andrade Teixeira Mota (2022)
This document aims to portray the process of Professional Internship (EP), inserted in the 2nd year of the Master in Physical Education Teaching in middle school and high school Education, at the Faculty of Sports of the University of Porto (FADEUP). The EP is the starting point in which the Intern Student (EE) has the first experiences of what it really means to be a teacher. The first contact with a reality that we are not used to, beyond having to interact with concrete and real students and their parents. During this process, setbacks arose that I had to adapt to and that contributed to the construction of my own identity, charting my path as a teacher, learning how to be an active part in the academic and personal training of students. Being a teacher is much more than just imparting knowledge. A teacher must be an example in leadership, inside and outside the classroom, and a role model in terms of values and life principles. Thus, this report will be divided into six main points: the first refers to the introduction and will contextualize the entire document; the second with regard to the personal framework, which will be portrayed my personal, academic and professional path, as well as the expectations at the beginning and throughout the internship; the third refers to the professional framework, which characterizes the school, the class that I taught PE and EN. The fourth refers to the accomplishment of the professional practice where the teaching-learning process will be portrayed throughout the school year; the fifth point is dedicated to the research study on the effect of functional training, carried out in Physical Education classes, on physical skills, measured through the FITescola tests and, finally, the sixth point where a final reflection of the EP will be portrayed and perspectives for the future.